The Utilization of Access Management to Digital Collections: Requirements & Challenges by Law - Koko Srimulyo; Yula Anggriani; Faizal Kurniawan (Unissula, 2024)
The spirit of Article 4 of Law No. 43 of 2007 is regulated by Article 5 paragraph (3) of Law No. 3 of 2017 is concerning to increase users interest in reading by converting printed books into electronic books. However, this breakthrough also brings new legal issues, namely the potential for reduced economic rights of creators or copyright holders of printed books as well as the decentralization of authority to convert printed books into physical books by libraries even though these requirements have been regulated by Article 27 of Law No. 28 of 2014 concerning Copyright; there is still room for illegal duplication and even piracy. There are two methods used in this research. The statutory approach is used to review statutory regulations primarily and the conceptual approach is used to support the narrative text presentation with relevant scientific literature. The results of this research indicate a need for special regulations regarding the conversion of printed books into electronic books by libraries by paying attention to the Economic Rights of the Creator or Copyright Holder of printed books. In addition, conversions must be carried out under the supervision of the relevant institutions and submitted centrally to the National Library to ensure standard procedures and conversion quality, and reformulation of previous regulations is necessary.